The differential impact of aerobic and isometric handgrip exercise on blood pressure variability and central aortic blood pressure. Issue 7 (July 2021) - Seidel, Maximilian; Pagonas, Nikolaos; Seibert, Felix S.; Bauer, Frederic; Rohn, Benjamin; Vlatsas, Stergios; Mühlberger, Dominic; Nina, Babel; Westhoff, Timm H.
Abstract : Background: Blood pressure variability and central SBP are independent markers of cardiovascular risk. Data on lifestyle-interventions to reduce these parameters are sparse. The present work reports the differential effects of aerobic vs. isometric handgrip exercise on blood pressure variability and central SBP in a prospective randomized trial. Methods: Seventy-five hypertensive patients were randomized to one of the following 12-week programs: isometric handgrip training five times weekly; 'Sham-handgrip training' five times weekly; aerobic exercise training (30 min three to five times/week). Blood pressure variability was assessed by the coefficient of variation in 24-h ambulatory blood pressure monitoring (ABPM). Central SBP was measured noninvasively by the SphygmoCor device (AtCor Medical, Australia). Results: The aerobic exercise program significantly decreased systolic daytime variability (12.1 ± 2.5 vs. 10.3 ± 2.8, P  = 0.04), whereas diastolic daytime blood pressure variability was not significantly altered ( P  = 0.14). Night-time variability was not significantly affected ( P  > 0.05). Central SBP was reduced from 145±15 to 134 ± 19 mmHg ( P  = 0.01). Isometric handgrip and sham-handgrip exercise did not significantly affect blood pressure variability ( P  > 0.05 each). Isometric exercise tended to reduce central SBP (142 ± 19 to 136 ± 17 mmHg, P  = 0.06). ANCOVA revealed significant intergroup differences for the change of daytime SBP and DBP variability ( P  = 0.048 and 0.047, respectively). Conclusion: Aerobic exercise reduces blood pressure variability and central SBP. Isometric handgrip exercise does not reduce blood pressure variability but tends to lower central SBP in this hypertensive population.